Genetic Association Study in Multigenerational Kindreds With Vasovagal Syncope: Evidence for Involvement of Sex-Specific Serotonin Signaling. (January 2019) - Sheldon, Robert; Rose, M. Sarah; Ritchie, Debbie; Martens, Kristina; Maxey, Connor; Jagers, Jennie; Parboosingh, Jillian; Gerull, Brenda
Abstract : Background: Several studies suggest that vasovagal syncope has a genetic origin, but this is unclear. We assessed whether plausible gene variants associate with vasovagal syncope. Methods: We studied 160 subjects in 9 kindreds comprising 82 fainters and 78 controls. The diagnosis was ascertained with the Calgary Syncope Score. Common genetic variants were genotyped for 12 genes for vascular signaling, potassium channels, the HTR1A (serotonin 5-HT1A receptor), SLC6A4 (serotonin reuptake transporter), and COMT (catecholamine O-methyltransferase). Sex-specific associations between genotypes and phenotypes were tested. Results: In 9 out of 12 variants, there was no significant association between genotype and phenotype. However, the HTR1A (−1019) G alleles associated with syncope in males, but not in females ( P =0.005). CC and GG males had 9% versus 77% likelihoods of syncope. The SLC6A4 promoter L alleles associated with decreased syncope in males but increased in females ( P =0.059). The LL and SS males had 25% and 47% syncope likelihoods, whereas females had 75% and 50% syncope likelihoods. The COMT c.472 A alleles associated with decreased syncope in males but increased in females ( P =0.017). The GG and AA males had 50% and 15% syncope likelihoods, whereas females had 52% and 73% syncope likelihoods. Conclusions: There is a sex-dependent effect of alleles of serotonin signaling and vasovagal syncope, supporting the serotonin hypothesis of the physiology of vasovagal syncope.